The American Heart Association’s Get With the Guidelines (GWTG)-Stroke development and impact on stroke care - Cora Ormseth; Kevin N. Sheth; Jeffrey L. Saver; Gregg C. Fonarow; Lee H. Schwamm (2017)
The American Heart Association’s Get With the Guidelines (GWTG)-Stroke programme has changed stroke care delivery in the USA since its establishment in 2003. GWTG is a voluntary registry and continuous quality improvement initiative that collects data on patient characteristics, hospital adherence to guidelines and inpatient outcomes. Implementation of the programme saw increased provision of evidence-based care and improved patient outcomes. This review will describe the development of the programme and discuss the impact on stroke outcomes and transformation of stroke care delivery that followed its implementation.